1997
DOI: 10.2165/00044011-199713020-00005
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacoeconomic Evaluation of Tegafur-Uracil (UFT) vs Fluorouracil for the Management of Colorectal Cancer in Brazil and Argentina

Abstract: The treatment of colorectal cancer continues to pose major challenges for oncologists throughout the world. Uracil and tegafur (UFT), as an oral agent, represents a new patient-focused approach to managing a malignancy with few treatment alternatives other than an intravenous fluorouracil (5-FU)-based regimen. The ability of UFT to achieve equivalent clinical outcomes compared with continuous 5-FU infusion, along with its oral formulation and mild toxicity profile, provide a compelling backdrop for fiscal anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1998
1998
2007
2007

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…treatment . UFT may be administered without visits to the hospital, resulting in reduced treatment costs (Murad et al, 1997) and increased convenience for the patient. The oral schedule also allows patients to temporarily withhold a dose of the drug if adverse events emerge, for example grade 2 diarrhoea, thereby preventing the toxicity from becoming severe.…”
Section: Discussionmentioning
confidence: 99%
“…treatment . UFT may be administered without visits to the hospital, resulting in reduced treatment costs (Murad et al, 1997) and increased convenience for the patient. The oral schedule also allows patients to temporarily withhold a dose of the drug if adverse events emerge, for example grade 2 diarrhoea, thereby preventing the toxicity from becoming severe.…”
Section: Discussionmentioning
confidence: 99%
“…Two economic evaluations by Murad and colleagues 51,52 were found, based on the same South American study comparing UFT with 5-FU. Two resource use studies were also identified, one relating to medical resource use in the two capecitabine trials 53 and one to resource use in the Carmichael UFT/LV trial.…”
Section: Identification Of Studiesmentioning
confidence: 99%
“…Murad and colleagues, 1997 51,52 An economic evaluation was undertaken of the treatment of patients with colorectal cancer in Brazil and Argentina. This study estimated the total cost of a course of treatment over 18 months with UFT/LV compared with a course of treatment with 5-FU.…”
Section: Review Of Existing Economic Evidencementioning
confidence: 99%
See 2 more Smart Citations